Socks from the toe up : essential techniques and patterns from Wendy Knits - Johnson, Wendy D. (Knitter) (New York : Potter Craft, 2009)
Wendy Johnson explains her technique for knitting socks from the toe up, looks at the pros and cons of other sock-knitting methods, and includes over twenty sock patterns
Includes index.
Keywords: Knitting -- Patterns; Socks